Psychometric properties of Psychosocial Inventory for Caregivers (PIC) scale - Abhijeet Singh; Arif Ali (Indian Journal of Psychiatry)
Background: There are various psychosocial challenges associated with caregiving in persons with mental illness. So, the present study attempts to develop a 62 itemed Psychosocial Inventory for Caregivers (PIC) scale in order to assess the different psychosocial problems in caregivers of persons with mental illness. Aim and Objective: The study aims to develop and test the PIC scale in a population with the objective to assess its reliability and validity. Methodology: The present study used a cross-sectional descriptive research design. Caregivers of persons with mental illness were the samples for the present study. Convenient sampling was used to collect 340 samples, based on the item-to-response ratio of 1:4. The study was conducted in the in-patient/out-patient department of LGBRIMH, Tezpur, Assam. Permission to conduct the study was taken from Institutes Ethics Committee (IEC). Proper written consent was taken from the participants after explaining to them the study. Result: Confirmatory factor analysis (CFA) was performed in SPSS version 25.0. The internal consistency of the PIC scale was found to be 0.88. The convergent validity of the PIC scale was acceptable because the average variance extracted (AVE) was above 0.50. The square root of the average variance explained was greater than the inter-factor correlation of the PIC scale, hence, discriminant validity was established. Conclusion: With the development of a PIC scale, a comprehensive assessment can be done to know the various factors and consequences related to caregivers of a person with mental illness.